A Rare Case of Paraprostatic Cyst in a Doberman Dog - Gondaliya, Ravi; Patel, Rajkumar; Patel , Nidhi; Sadhu, Dashrath B.; Raval, Sunant K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The majority of prostate diseases are observed in middleaged or older intact male dogs. Large and medium-sized breeds particularly German shepherd and Doberman pincher seem to be frequently affected (Krawiec and Heflin, 1992). The most diagnosed prostatic disease is benign prostatic hyperplasia, followed by prostatitis, while abscesses, neoplasms, and prostatic cysts are extremely rare